Exploring basic and integrated science process skills and their impact on science achievement among university students - Kamarudin, Nurzatulshima; Mariyam Wahida; Ahrari, Seyedali (Macrothink Institute, 2022)
Learning science is important to gain a broader view and clear understanding of the complex world. This study aimed to examine the effect of the level of understanding of basic and integrated science process skills (SPSs) on student science achievement. The test instrument was administered to measure the level of understanding of basic and integrated SPSs from 73 students studying in the Science Foundation Studies Program. Findings: The findings of the study reveal level of understanding of basic science processes was satisfactory whereas integrated science process skill was poor. A moderate correlation was found between basic SPSs and integrated SPSs. A weak positive correlation was found between basic SPSs and science achievement. There was an insignificant correlation between integrated SPSs and science achievement. The level of understanding of SPSs among both females and males was fair with females and males. The results of the independent sample t-test indicated there were no significant differences in the level of understanding of SPSs between females and males. It is hoped that the findings provide insight into the ability level of students and would be useful to bring a positive change in the Foundation Studies Program.